Glycoprotein VI is not a Functional Platelet Receptor for Fibrin Formed in Plasma or Blood - Zhang, Danmei; Ebrahim, Mariam; Adler, Kristin; Blanchet, Xavier; Jamasbi, Janina; Megens, Remco T. A.; Uhland, Kerstin; Ungerer, Martin; Münch, Götz; Deckmyn, Hans; Weber, Christian; Elia, Natalie; Lorenz, Reinhard; Siess, Wolfgang (Thrombosis and Haemostasis, 2020)
Glycoprotein VI (GPVI), a platelet collagen receptor, is crucial in mediating atherothrombosis. Besides collagen, injured plaques expose tissue factor (TF) that triggers fibrin formation. Previous studies reported that GPVI also is a platelet receptor for fibrinogen and fibrin. We studied the effect of anti-GPVI antibodies and inhibitors of GPVI signaling kinases (Syk and Btk) on platelet adhesion and aggregate formation onto immobilized fibrinogen and different types of fibrin under arterial flow conditions. Fibrin was prepared from isolated fibrinogen (“pure fibrin”), recombinant fibrinogen (“recombinant fibrin”), or generated more physiologically from endogenous fibrinogen in plasma (“plasma fibrin”) or by exposing TF-coated surfaces to flowing blood (“blood fibrin”). Inhibition of GPVI and Syk did not inhibit platelet adhesion and aggregate formation onto fibrinogen. In contrast anti-GPVI antibodies, inhibitors of Syk and Btk and the anti-GPIb antibody 6B4 inhibited platelet aggregate formation onto pure and recombinant fibrin. However, inhibition of GPVI and GPVI signaling did not significantly reduce platelet coverage of plasma fibrin and blood fibrin. Plasma fibrin contained many proteins incorporated during clot formation. Advanced optical imaging revealed plasma fibrin as a spongiform cushion with thicker, knotty, and long fibers and little activation of adhering platelets. Albumin intercalated in plasma fibrin fibers left only little space for platelet attachment. Pure fibrin was different showing a dense mesh of thin fibers with strongly activated platelets. We conclude that fibrin formed in plasma and blood contains plasma proteins shielding GPVI-activating epitopes. Our findings do not support a role of GPVI for platelet activation by physiologic fibrin.
Keywords: Glycoprotein VI; platelet; fibrinogen/fibrin; atherothrombosis; glycoprotein Ib